VLAN-based LAN Network Management Comparison using Cisco and Brocade - Ramadhan Gatra; Reonaldo Akbar; Bambang Sugiantoro; Naufal Asyhab (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2018)
The need for security and convenience in carrying out data requires all users to be able to create a safer network, in terms of both data communication and sharing internet connection lines. The effectiveness of performance in work is always required to be able to work quickly and on time without the constraints of high data traffic that may cause problems in network devices. Those problems may ultimately cause all work to be hampered in its completion. Management of VLANs in a LAN connection is able to parse problems especially in terms of data communication and logical data transmission. This paper studies on this issue.